EKSISTENSI MENGGUGAT PROSEDUR DISMISSAL PADA PERADILAN TATA USAHA NEGARA - I Gede Kuntara Sidi; Anak Agung Ngurah Yusa Darmadhi (Kertha Negara : Journal Ilmu Hukum, 2014)
State Administrative Court (Administrative Court) is a special court to resolve thedispute between the government and the judge as the executor state with societybecause of the decisions issued by the government. Since the establishment of the court,be a public expectation to people who are weak, to fight the government's decision thatdamaged their rights through the courts that the initiative of the authorities. However,the process of dismissal on legal court procedure gives competence to the chairman ofthe court to reject the government's allegations were investigated before a decision bythe judge in a hearing open to the public. The termination process has extended the timefor action and add loads Plaintiff to justice, of course it has decreased the meaning ofthe Administrative Court that the expectations of society in order to protect the publicand bring about justice in the Republic of Indonesia.